Penerapan Sistem Informasi Manajemen Daerah Keuangan Dalam Pengelolaan Data Keuangan Pada Organisasi Pemerintah Daerah (Studi Kasus Pada BPBD Kabupaten Magelang) - Herlina Damayanti; Rian Destiningsih (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
Technological developments encourage the government to advance computer-based information systems to make it easier for the government to manage finances. A Regional Management System application called SIMDA was developed. SIMDA Finance is a technology that has been used by almost all regional governments in Indonesia when carrying out the related regional financial arrangements themselves. The purpose of this study is to see how the effect of the implementation of SIMDA Finance on the quality of financial reports in BPBD Magelang Regency. This study analyzes the application of SIMDA Finance in one of the SKPDs of Magelang Regency, namely BPBD of Magelang Regency. This research was conducted with a quantitative approach. The data in the current research are primary data types. The data collection system by distributing questionnaires / questionnaires to some employees in BPBD Kab. Magelang which was held in January-February 2020. The results showed that the variable of SIMDA Financial Implementation influenced the Quality of Financial Statements positively and significantly in the Regional Disaster Management Agency SKPD of Magelang Regency in 2020. With a statistical t value of 2.813843 1.895 (t table ), which means that the SIMDA Financial variable (X) affects the Quality of Financial Statements (Y).